Stress dynamics of architecture students during jury presentations: an exploratory EDA study - Er, Ihsan Erdem; Heyik, Muhammet Ali; Tastan, Hasan; Arabacioglu, Feride Pinar (SPRINGER, 2026)
This study investigates physiological stress dynamics during architectural jury sessions (AJS) using Arduino-based electrodermal activity (EDA) sensors. It examines the relationship between physiological stress, communication patterns, and jury performance. A quantitatively driven exploratory design was adopted. Physiological stress was measured through EDA values, behavioral data were analyzed using dual-coded content analysis of communication tone and direction, and performance was evaluated based on students' jury grades. Results showed that physiological stress levels (EDA) increased after jury sessions for both novice and senior students. Among novices, stress was highest during one-sided presentation moments where students spoke very little, suggesting that limited opportunity for self-expression heightened stress. No significant relationship was found between communication tone and stress, or between stress and performance. These findings indicate the evaluative intensity of architectural juries and emphasize the need for communication-focused pedagogical strategies to support students during design critiques.
Keywords: Architectural jury; Stress; EDA; Content analysis; ELECTRODERMAL ACTIVITY; ENGINEERING STUDENTS; HEART-RATE; DESIGN; TEMPERATURE; PERCEPTIONS; DEPRESSION; MOTIVATION; FEEDBACK; Education & Educational Research; Engineering